Searched refs:BaseF (Results 1 – 1 of 1) sorted by relevance
1935 const APFloat *BaseF; in replacePowWithExp() local1936 if (!match(Pow->getArgOperand(0), m_APFloat(BaseF))) in replacePowWithExp()1955 BaseR.convert(BaseF->getSemantics(), APFloat::rmTowardZero, &Ignored); in replacePowWithExp()1956 BaseR = BaseR / *BaseF; in replacePowWithExp()1957 bool IsInteger = BaseF->isInteger(), IsReciprocal = BaseR.isInteger(); in replacePowWithExp()1958 const APFloat *NF = IsReciprocal ? &BaseR : BaseF; in replacePowWithExp()1986 if (Pow->hasApproxFunc() && Pow->hasNoNaNs() && BaseF->isFiniteNonZero() && in replacePowWithExp()1987 !BaseF->isNegative()) { in replacePowWithExp()1995 Log = ConstantFP::get(Ty, std::log2(BaseF->convertToFloat())); in replacePowWithExp()1997 Log = ConstantFP::get(Ty, std::log2(BaseF->convertToDouble())); in replacePowWithExp()